The rapid increase in telemedicine visits during COVID-19 - Chelsea Johnson (The Beryl Institute, 2020)
Prior to the COVID-19 pandemic, facilitated telemedicine encounters were available at outreach locations; however, our tertiary children’s hospital had not invested widely in direct to patient telemedicine. Our daily pediatric subspecialty visits dropped from an average of 2066 visits a day prior to COVID-19 in our community to 1000 patients a day during the study period. Over the four-week period from April 15 to May 12, 2020, patient and family experience ratings of percentage of positive responses (9 or 10) on the provider rating 0-10 scale between telemedicine and in-person visits were compared for our pediatric subspecialty clinics using a Pearson’s Chi Squared test, p-value <0.05 determined significance. Several process measures were compared using the same method. Total visits conducted via telemedicine and survey response rates were calculated with frequencies and percentages. Of the 14,428 subspecialty visits attended, 10,135 (70.2%) were telemedicine. Developmental and Behavioral Medicine saw the highest proportion of patients (99.5%) via telemedicine while Cystic Fibrosis, Dentistry, and Neurosurgery saw no telemedicine patients. Telemedicine visits yielded a 6.5% higher survey response rate than in-person visits. Overall rating of 9 or 10 for telemedicine visits was 87.9%, compared to 83.9% for in-person visits (p-value = 0.07). All process measures scored higher in telemedicine visits. This may reflect telemedicine visits’ ability to improve the efficiency of care delivery: removing the need to travel, park, navigate the building, register for the visit, obtain vital signs and wait for the provider. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens